Participação do córtex dorsal reptiliano nos processos de aquisição, consolidação e evocação da memória aversiva no lagarto Tropidurus hispidus (Spix, 1825) - Santos, Edson Lima (2018)
The aversive memories context are extremely important for animal survival in the environment. In mammals, for example, encephalic regions such as the amygdala and hippocampus have essential role in aversive memory formation. However, in reptiles group, even with brain homologies to mammals, there are few studies about this type of memory formation processes. The aim of the present study was to evaluate the reptilian dorsal cortex involvement in the aversive memory of lizard Tropidurus hispidus. Thirty-six adult male lizards were used. The animals were submitted to stereotaxic surgery for guide cannulas implantation in the region of dorsal cortex. Seven days later, the animals were separated into two groups: Control (CTR) and Muscimol (MUS), which were distributed in three experiments: Experiment I - aversive memory acquisition (1 microinjection of MUS (n = 6) or saline (n = 6), 15 'before training) ; Experiment II - aversive memory consolidation (1 microinjection of MUS (n = 7) or saline (n = 7) soon after training session); and Experiment III - aversive memory evocation (1 microinjection of MUS (n = 5) or saline (n = 5), 15 'before the test session). The animals were submitted to a square open field task, divided into two sessions: training and test, with a 24 h interval. For each session, the animals passed through the habituation and exposure phases (10' each). On training, the habituation phase corresponded to the animal's exploration time in the apparatus, while the exposure phase was characterized by the presentation of a barred cage containing a domestic cat. On test, the procedures were similar to training, however, in the exposure phase, the animals were presented only to the empty cage. The results were similar in the both experiments. It was observed that the animals of MUS group from both experiments showed higher freezing time (p <0.05) and latency (P <0.05) for performing movement in the first exposure phase compared to the training habituation. In the test exposure, there was no difference between MUS or CTR groups for freezing (p = 0.125, p = 0.375, I and II, respectively) and latency (p = 0.437, p = 0.187, I and II, respectively). In experiment III, we observed that the animals of MUS group, during training exposition phase, showed higher freezing time (p <0.05), lower visited quadrants number (p <0.05) and higher and initiated displacements (p <0.05) when compared to the habituation phase. In the exposure phase of test, the animals did not show this increase (p = 0.312, p = 0.250 e p = 0.315, respectively). Therefore, the present study showed evidences that the reptilian dorsal cortex of T. hispidus influenced the acquisition, consolidation and evocation of aversive memory processes, but it seems that did not interfere in the animals present with aversive responses process.